Evaluation of Antioxidative Potential of the Biofield Energy Treated Proprietary Test Formulation on L-NAME and High Fat Diet-Induced Cardiovascular Disorders in Sprague Dawley Rats - Kumar Trivedi, Mahendra; Branton, Alice; Trivedi, Dahryn; Jana, Snehasis (Journal of Antioxidant Activity, 2021)
The aim of this experiment was to assess the antioxidative potential of the Biofield Energy Treated/Blessed Proprietary Test Formulation and Biofield Energy Treatment/Blessing per se to the animals on NG-nitro-L-arginine methyl ester hydrochloride (L-NAME) and high fat diet (HFD)-induced cardiovascular disorders in Sprague Dawley rats using various functional biomarkers. A test formulation was formulated including minerals (magnesium, zinc, copper, calcium, selenium, and iron), vitamins (ascorbic acid, pyridoxine HCl, vitamin B9, vitamin B12, and vitamin D3), cannabidiol (CBD) isolate, Panax ginseng extract, and β-carotene. The test formulation’s constituents were divided into two parts; one part was denoted as the untreated, while the other part and three group of animals received Biofield Energy Healing/Blessing Treatment remotely for about 3 minutes by a renowned spiritual leader, Mr. Mahendra Kumar Trivedi. The expression of superoxide dismutase (SOD) was elevated significantly by 198.46%, 208.73%, 191.73%, 211.75%, and 198.82% in the G5 (L-NAME + HFD + the Biofield Energy Treated test formulation), G6 (L-NAME + HFD + Biofield Energy Treatment per se to animals from day -15), G7 (L-NAME + HFD + the Biofield Energy Treated test formulation from day -15), G8 (L-NAME + HFD + Biofield Energy Treatment per se plus the Biofield Energy Treated test formulation from day -15), and G9 (L-NAME + HFD + Biofield Energy Treatment per se animals plus the untreated test formulation) groups, respectively than disease control group (G2). Moreover, the level of glutathione peroxidase (GPx) was significantly increased by 61.94%, 118.49%, 82.96%, 141.89%, and 262.02% in the G5, G6, G7, G8, and G9 groups, respectively as compared to the G2 group. Lipid peroxidase (LPO) was decreased by 14.21%, 30.98%, 38.66%, and 32.67% in the G6, G7, G8, and G9 groups, respectively than G2 group. Additionally, the level of myeloperoxidase (MPO) was decreased by 28.46%, 10.87%, 12.41%, and 13.35% in the G6, G7, G8, and G9 groups, respectively than G2. Further, the level of oxidized low density lipoprotein (LDL) was reduced by 65.38%, 65.11%, 71.53%, 79.26%, and 66.57% in the G5, G6, G7, G8, and G9 groups, respectively than G2. Besides, in heart tissues, the level of catalase (CAT) was significantly increased by 68.20%, 63.69%, 126.03%, 124.54%, and 112.23% in G5, G6, G7, G8, and G9 groups, respectively than G2 group. Moreover, in kidney tissues, the level of CAT was significantly increased by 22.48%, 23.43%, and 10.95% in the G6, G7, and G9 groups, respectively than G2. Overall, the data suggested a significant antioxidant activity by increasing the levels of SOD, CAT, GPx, and reducing the levels of LPO, MPO, and oxidized-LDL in various tissue fluids and that might be beneficial for cardiovascular disorders. Therefore, the study outcomes showed the significant slowdown the oxidative stress-related cardiovascular disease progression and its complications in the preventive treatment groups viz. G6, G7, G8, and G9.
Keywords: Antioxidant; Superoxide Dismutase; L-NAME; High Fat Diet; Cardiovascular Disorders; Sprague Dawley Rats